Present yourself : using SlideShare to grow your business - Seeborg, Kit (O'Reilly, 2013)
With the success of SlideShare and other online presentation sites, slide presentations have become the language of business. This practical book demonstrates how you can use this visual language to make the story of your organization, brand, or initiative effective and entertaining--and how social sharing networks like SlideShare, Prezi, and Scribd can present your story to a worldwide audience. Using real-world examples from SlideShare users, Present Yourself puts marketing principles and business trends in context to help you understand how online presentations can boost your business. The final chapter provides case studies that reveal how organizations and individuals use SlideShare to meet their needs. Learn the latest trends and technologies for visual communication in business Discover how SlideShare works, and get started with your own account Use SlideShare to plan, execute, and provide follow-up for event presentations Share your wealth of content to promote trust in your company or brand Anticipate a customer's needs with knowledge-rich content about their market Collaborate with colleagues and conduct online business research Explore how presentations can help you recruit, hire, or get hired.